Relationship of Nutritional Status with Permanent Tooth Eruption in Primary School-Age Children (6-12 Years) Literature Study Review - Alfah, Siti; Armita Linda Indryani; Junaidin; Nur Ekawati; Sangkala (Jurusan Kesehatan Gigi Poltekkes Kemenkes Aceh, 2023)
Nutritional status is a requirement to determine whether a person is in a healthy state which is influenced by several factors, namely diet and adequacy of nutrients to carry out a normal metabolism. Some nutrients that can affect the growth and development of tooth eruption time include the large intake of vitamin D, calcium, phosphorus, and flour in the body. Deficiencies in nutrients can inhibit the process of tooth growth and development and slow down the time of tooth eruption. Tooth eruption is the process of moving teeth from the jawbone towards the oral cavity. Tooth eruption can be influenced by several factors, one of which is the nutritional status which is the state of the body as a result of food consumption and the use of nutrients. The purpose of this study was to elaborate on the relationship of nutritional status with permanent tooth eruptions in children of primary school age (6-12 years). This type of research uses a type of literature study research. Journal searches were conducted from 2017-2022 on Google Scholar and Pubmed databases in Indonesian and English. Journal search strategies use the keywords